Stability of cylindrical steel silos composed of corrugated sheets and columns based on FE analyses versus Eurocode 3 approach. (November 2015) - Iwicki, P.; Rejowski, K.; Tejchman, J.
Abstract: Comprehensive static and dynamic 3D stability finite element analyses of a cylindrical steel silo composed of corrugated sheets and open thin-walled vertical stiffener profiles were carried out by taking the geometric and material non-linearity into account. The silo was subjected to axisymmetric and non-axisymmetric loads imposed by a bulk solid following Eurocode 1. Theoretical and measured initial geometric imperfections were considered in calculations. The results of non-linear analyses were compared to those according to Eurocode 3. Modifications of the Eurocode formulae were proposed. Some recommendations for the silo engineering design were elaborated. Graphical abstract: Comprehensive static and dynamic 3D stability FE analyses of a cylindrical steel silo composed of corrugated sheets and vertical stiffeners were carried out by taking the geometric and material non-linearity. The silo was subjected to axisymmetric and non-axisymmetric loads imposed by a bulk solid following Eurocode 1. Theoretical and measured initial geometric imperfections were considered in calculations. The differences between static and dynamic analysis results were discussed. The results of non-linear analyses were compared to those according to Eurocode 3. A modification of the Eurocode formulae was proposed. Some recommendations for the silo engineering design were elaborated. Highlights: We deal with stability of large cylindrical metal silos composed of corrugated sheets. We carry out 3D FE stability calculations with the finite element method. We compare our FE results with the Eurocode approach. A modification of the Eurocode formulae was proposed.